COMPARISON OF SURGICAL TEMPLATES THAT ARE USED BY DENTAL IMPLANTS - Руфат Акіф Огли Гусейнлі (World of Medicine and Biology, 2016)
A group of patients involving 260 people who had defects of dentition upper and lower jaw was examined. Patients were divided into 2 groups, 130 people each. For patients from the first group a roentgenopaque acrylic surgical templates using of barium sulfate have been produced. For patients from the second group not-roentgenopaque acrylic surgical template with the additional use of radiopaque markers have been produced. A new method of preoperative evaluation of patients allows for early diagnosis to take into account the parameters of bone tissue, including bone density, height, width, distance to antivirusi teeth and the occlusal plane was developed. This technique allows to optimize surgical tactics in various defects of bone tissue. A new type of surgical templates allowing to transfer data received in the result of inspection to the operative field with minimal deviations and creating the opportunity to avoid complications at the stage of surgical intervention was developed.